The Implementation of Betawi Language as an Endangered Language - Wulan Permandani; Iskandarsyah Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The Betawi language, the native tongue of Jakarta's original community, is currently facing a critical situation due to the fast-paced developments in the city's civilization. As a result, urgent and effective preservation measures are necessary to safeguard the Betawi language. Concerns arise from the fear that the Betawi language might vanish and become extinct, leading to the failure of passing down Betawi values, technology, traditions, and culture to future generations. Losing these traditional values and cultural heritage would mean the decline of an entire civilization. The research aims to evaluate the present condition and status of the Betawi language and employs Social Semiotics, Demography, and Sociology as its main disciplines. To avoid being solely reliant on numbers, a qualitative approach is adopted, focusing on expression, nuances, and preferences. The findings of this research indicate that the current state of the Betawi language is more precarious than in the past, and its negative impact on the Betawi community is significant. However, it is believed that the educational approach holds promise in supporting efforts to preserve the Betawi language. Nevertheless, a comprehensive preservation strategy should be developed, with collaboration from various contextual segments to ensure the survival of the Betawi language.